Stable copd management in relation to the GOLD: Experience at a university hospital (2008)
Introduction: This paper presents a prospective and descriptive study discussing the outpatient care plan in a public hospital in Bogotá for patients with stable COPD according with the GOLD recommendations. The paper presents as well the influence of factors such as education, pharmacological treatment, pulmonary rehabilitation and oxygen-therapy. A survey was carried out among patients, and the results were evaluated and validated by a group of experts; a personal data card for the review of clinical records was considered. Materials and methods: This is a three-phase study. On the first phase, selected patients from outpatient care visits were included with a primary diagnosis of COPD on the stable condition stage; these patients had no evident exacerbation in at least one month before the survey. Clinical records, demographic data (gender, age), previous control dates, required examinations, prescribed medicines, referral to pulmonary rehabilitation programs, exercises and domiciliary oxygen-therapy were recorded. On the second phase, the survey was carried out among 61 adult patients who met the inclusion criteria and the clinical record register. On the third phase, the analysis and interpretation of the results were carried out with a statistic processing of the information, which considers multivariate and univariate data analysis using the software SPSS version 11.5 for Windows. Results: The number of patients with COPD diagnosis studied during the research period of time in our hospital outpatient service was 69, however only 61 of them fulfilled all the inclusion criteria. Sixty-one patients were interviewed, average age, 73. Seventy percent were female. Fifty percent of the participants were from low schooling, social and economic segments of the population; 50% had no formal education and 93% were family dependent. The major risk factor reported (84%) was wood fire smoke, with an average exposure of more than 20 years (72%). Thirty percent considered that they had been educated about their disease by a physician, 47% used inhaled bronchodilators, 48% of whom had difficulties to obtain them. Although 56% of all patients were using home oxygen therapy, and 93% suffered some degree of dyspnea, only one patient had undergone pulmonary rehabilitation. Conclusions: Our study revealed that non pharmacological therapy and patient education do not meet GOLD recommendations at a Colombian public hospital; this is due, in part, to inadequacies of the public health system and accessibility to it, lack of clinical guidelines, scant medical referral and heavy patients load. It is necessary to implement an improvement plan that will enhance COPD patient treatment and expand heath care professionals participation in it. © 2008 Corporación Editora Médica del Valle.